Penyelesaian Konflik Penguasaan Tanah HGU dengan Masyarakat di Bengkulu Utara - Anggriawan, Rosi Pramula; Sutaryono, Sutaryono; Salim, M. Nazir (Sekolah Tinggi Pertanahan Nasional, 2021)
The increasing number of land conflicts, particularly over HGU (Hak Guna Usaha/Right to Cultivate) land, has far-reaching implications for the community. On the one hand, the community requires land, while on the other, the company seeks to defend what they consider are their rights. Because this argument attracts others, it is necessary for a government agency to act as a referee or facilitator to resolve the resulting conflict. The purpose of this study was to identify the factors that contribute to land tenure conflicts between the community and three companies that own HGU, as well as to explain the role of the Ministry of ATR/BPN in resolving those conflicts. The data collection method used in this study was a qualitative one presented in a descriptive manner, followed by a comparative/comparative analysis of the cases. The results suggested that the conflict arose because community members were inneed of land reclaimed on HGU land, while HGU holders made a little positive contribution to the residents surrounding the plantation. With regards to this situation, the Ministry of ATR/BPN attempted to resolve it through relatively effective methods, namely acting as a mediator and negotiator, delaying the HGU extension process, and eventually distributing some of it to the community. The partial efforts made thus far have been relatively effective and provide a sense of security for the landowners.